Journal for artistic research - Society for Artistic Research (Y (Institute for Transdisciplinarity), Bern University of the Arts, 2011)
The Journal for Artistic Research (JAR) is an inter-national, online, Open Access and peer-reviewed journal for the identification, publication and dissemination of artistic research and its methodologies, from all arts disciplines.
Keywords: Art : Research : Periodicals; Art : Methodology; Art : Recherche : Périodiques; Art : Méthodologie; Art : Research